The Chuquibamba Landslide Western Cordillera, Peru revisited: New Evidence of a Dry Debris Avalanche - Juan Manuel Sánchez-Núñez; José Luis Macías Vázquez; José Luis Arce-Saldaña; Juan Carlos Gómez (Geofísica Internacional)
Landslides represent a serious mountain hazard to lives and infrastructure, especially when geological factors such as highly fractured rocks, faulting, steep topography, and weathering combine with seismic triggering factors. Considering the potential of producing outcomes, we study the Chuquibamba rotational landslide that runs along the NW-SE Incapuquio-Challaviento fault system in southernmost Peru. Its elongated U-shaped and polylobate crown scarp is typical of fault-related landslides, and it is carved into the ignimbrites of the Chuquibamba Formation. The geomorphology of the failure and its associated deposit define seventeen coalescing rotational slides and a widespread debris avalanche. This deposit, the main topic of this study, dated at ca. 102 Å} 5 ka using 10Be (from previous works), is confined to the lower parts of the Grande River valley. It is exposed for about 22.5 km from 3,900 to 1,167 masl with its main front located at ~ 10 km upstream of the Majes River. It covers an area of 33.64 km2 with a minimum volume of 0.72 km3. The resulting deposit has an H/L = 0.12, which is typical of dry debris avalanches elsewhere. It consists of block and matrix facies that have different textural and granulometric features. At the time of its emplacement, the moving avalanche overpassed 20 and 12 m-high obstacles, attaining minimum speeds of 20 and 15 m/s at distances of 15 and 20 km from the source, respectively. After the landslide emplacement, the debris avalanche was re-mobilized by intense rains that produced debris flows, as attested by outcrops along the extension of the debris avalanche and beyond its front. All the features of the Chuquibamba dry avalanche, along with modern seismicity and the intersection of active faults in the region, suggest that the failure had a tectonic origin (uplift and movement along faults) instead of deglaciation, extraordinary rain, or extreme rock weathering. Therefore, landslide generation is a potential hazard in this area of Peru.